PENGARUH KONSENTRASI ASAP CAIR TEMPURUNG KENARI DAN LAMA PENYIMPANAN TERHADAP KUALITAS KIMIA DAN FISIK DAGING - Rizky Arizona; Edi Suryanto; Yuny Erwanto (Faculty of Animal Science, Universitas Gadjah Mada, 2011)
The objective of the experiment study was to determine the effect of canary shell liquid smoke on the chemical, physical and sensory qualities of beef stored at room temperature. Beef samples were dipped in liquid smoke solutionwith the concentration of 0, 4, 8, and 12% (v/v) during 15 minutes and then stored for 0,2, and 4 days at room temperature. Each treatment was carried out three times and the variables measured were water, phenol and acidcontent, pH, water-holding capacity, cooking loss and sensory properties of samples. Data on chemical and physical qualities were analyzed using analysis of variance (Completely Randomized Design/CRD) with factorial 4x3. Thesensory properties were analyzed by a non parametric h-test. The results showed that liquid smoke concentration up to 12% significantly (p<0.05) increased water holding capacity and cooking loss of samples. Storage time up to four dayssignificantly (p<0.05) increased its pH value, cooking loss, whereas water-holding capacity was decreased. The meat sensory test showed that flavor and slimming rate were affected significantly (p<0.05) by liquid smoke. There was nointeraction between liquid smoke concentration and storage time. In conclusion, the addition of liquid smoke up to 12% increased phenol and acid content, while the physical quality of meat has decreased. Quality of beef stored up to 4 daysshowed a decreased of quality such as pH, water-holding capacity, cooking loss, and sensory meat.(Keywords: Canary shell, Liquid smoke, Storage time, Quality of beef)